Port of Rotterdam in Chinese Eyes - Peter J. Peverelli (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2007)
The Port of Rotterdam is a typical European organisation that undertakes several activities towards China annually and has a clear understanding of what it has to offer to its Chinese counterparts, but does not always succeed in achieving rapport with those counterparts. This paper studies the identity constructs of the Port of Rotterdam in a selected number of Chinese contexts (central ministries, main ports, etc.). The methodology is narrative analysis using corpora of texts compiled for each context. The core theoretical principle1 is that identity is not a property, but a process of ongoing interaction. The identity of A can only be established in a particular context, by observing the interaction between A and parties in that context. A will thus obtain multiple identities in multiple contexts. The results can be used by the Port of Rotterdam to improve the effectiveness of its delegations to China.
hdl:10398/7406
Keywords: 330